Scaled simulation of the blast effects on structures using lego blocks: a pilot study - Critchley, Richard; Peare, Alan; Sheldon, Robert (Straightline Publishing Limited, 2018)
Blast effects on structures is an important topic in this modern age for many practising engineers, including structural engineers designing buildings for safety or weapons engineers attempting to destroy enemy infrastructure. Due to the large costs, time demands, space requirements and expertise required, full scale testing is rarely a feasible approach. As such it is important to be able to effectively model the blast effects on structures. Currently, computer modelling techniques are extensively used, however the results of these models are often difficult to verify, whilst requiring experienced expert users to ensure accurate data.